2018
DOI: 10.1177/0192512118755596
|View full text |Cite
|
Sign up to set email alerts
|

Three decades of the International Political Science Review (IPSR): A map of the methodological preferences in IPSR articles

Abstract: Where does the International Political Science Review (IPSR) stand in relation to the hierarchies of knowledge in the discipline? IPSR is the journal of the International Political Science Association and a well-established journal in the discipline of Political Science. The journal has been published since 1980 and in 2016 ranked 54 out of 163 journals in the field. Mapping IPSR’s profile can help us understand the changing thematic, epistemological and methodological preferences within the world of political… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
1
6
0
2
Order By: Relevance
“…With articles submitted from authors in 64 countries, and articles accepted from authors in 23 countries, in 2020, IPSR can stand over its claim to be a truly international journal, albeit with the caveat that the Global North is substantially over-represented among accepted authors, as is the case with many international journals. This pattern is long established as Lima et al (2018) demonstrated that North America and Western Europe accounted for three quarters of all articles since the foundation of the journal. Figure 1 highlights the top submitting countries for 2020 and Fig.…”
Section: Student Publishingmentioning
confidence: 96%
See 2 more Smart Citations
“…With articles submitted from authors in 64 countries, and articles accepted from authors in 23 countries, in 2020, IPSR can stand over its claim to be a truly international journal, albeit with the caveat that the Global North is substantially over-represented among accepted authors, as is the case with many international journals. This pattern is long established as Lima et al (2018) demonstrated that North America and Western Europe accounted for three quarters of all articles since the foundation of the journal. Figure 1 highlights the top submitting countries for 2020 and Fig.…”
Section: Student Publishingmentioning
confidence: 96%
“…The journal's pluralistic mission is evident in its commitment to publishing qualitative, quantitative and mixed‐method research, as well as small‐N and large‐N studies. Lima et al (2018) reported that IPSR is representative of publishing in the discipline of political science both in its approaches to the study of politics and its methodological diversity. The journal does not take a specific position on student publishing, it welcomes submission from all author types, on all political science topics and from all parts of the world.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…En otras palabras, persiste la insistencia en cooptar las teorías feministas bajo una lógica de ciencia 3 Es importante destacar que Marchand escribe desde una perspectiva europea acerca de la disciplina de RR.II. La apertura epistemológica que ella subraya en su texto, retrata una diversidad que requiere escrutinio empírico, especialmente considerándose hallazgos recientes acerca del dogmatismo metodológico y de la baja presencia de mujeres en las revistas científicas de Ciencia Política y Relaciones Internacionales (Lenine & Mörschbächer, 2020;Lima et al, 2018;Rocha Carpiuc, 2016;Teele & Thelen, 2017).…”
Section: Diálogos: ¿Concesiones Sinceras?unclassified
“…Há, nessa linha analítica, alguns estudos focados apenas em periódicos que permitem entender, por exemplo, as preferências metodológicas da Ciência Política (Kasza, 2010;Lima, Mörschbächer & Peres, 2018), as mudanças nos padrões de cientificidade e produção de inferências da área (Rezende, 2017) ou ainda o tipo de tratamento que um tema/região recebe (Cammett & Kendall, 2021). Análises críticas apoiadas em bibliometria, como a de Lenine e Mörschbächer (2020), destacam a produção de hierarquias de conhecimento e prestígio que são naturalizadas pela Ciência Política mundial e que funcionam como efeito e causa da "falta de pluralidade e diversidade de perfis profissionais na disciplina" (2020, p. 125).…”
Section: Análise E Autoanálise De Periódicos Científicos De Ciência Políticaunclassified